1986
DOI: 10.1002/cjce.5450640511
|View full text |Cite
|
Sign up to set email alerts
|

Anisole production by alkylation of phenol over ZSM5

Abstract: The alkylation of phenol with methanol was performed in a microcatalytic reactor using the H‐ and Na‐forms of a ZSM5 zeolite. Conditions were found in which the selectivity of the O‐alkylation yielding anisole was as high as 80%. Some results are also reported for the alkylation of 2,4‐dimethylphenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Various zeolites have been studied for this reaction. These include H-Y [7][8][9][10], H-ZSM-5 [7,[11][12][13], H-mordenite [6] and H-beta [14]. However, these zeolites have shown poor paraselectivity with p:o-cresol ratios not exceeding 0.7.…”
Section: Introductionmentioning
confidence: 92%
“…Various zeolites have been studied for this reaction. These include H-Y [7][8][9][10], H-ZSM-5 [7,[11][12][13], H-mordenite [6] and H-beta [14]. However, these zeolites have shown poor paraselectivity with p:o-cresol ratios not exceeding 0.7.…”
Section: Introductionmentioning
confidence: 92%
“…With MFI zeolites, at temperature higher than 350°C Kaliaguine et al [2,53] found that the reaction leads to a variety of products, amongst which the most relevant were cresols and xylenols. A mechanism was proposed in which diphenyl ether and anisole (the two products of etherification) are the reaction intermediates and interact with Brønsted sites and carbonium ions to yield C-methylated products.…”
Section: Catalyst Activity and Deactivation Ratementioning
confidence: 99%
“…Solid bases, in particular MgO, selectively alkylate phenol in ortho-position, producing essentially o-cresol and 2,6 xylenol [5,6]. Solid acids such as silicaalumina, Nafion-H resin, HPA/SiO 2 , and zeolites HBEA and HY, convert phenol to a mixture of anisole, cresols, xylenols and methylanisoles [7][8][9][10][11][12][13]. Brønsted solid acids promote the O-alkylation of phenol [10,11] while Lewis solid acids (SiO 2 -Al 2 O 3 ) and zeolites containing similar amounts of Lewis and Brønsted acid sites (HBEA, HY) favor the C-alkylation of phenol [7,14].…”
Section: Introductionmentioning
confidence: 99%